2011
DOI: 10.1103/physrevb.83.045106
|View full text |Cite
|
Sign up to set email alerts
|

Quantum critical metamagnetism of Sr3Ru2O

Abstract: Using ac susceptibility, we have determined the pressure dependence of the metamagnetic critical endpoint temperature T * for a field applied in the ab plane in the itinerant metamagnet Sr 3 Ru 2 O 7 . We find that T * falls monotonically to zero as pressure increases, producing a quantum critical endpoint (QCEP) at P c ∼ 13.6 ± 0.2 kbar. New features are observed near the QCEP-the slope of T * versus pressure changes at ∼12.8 kbar, and weak subsidiary maxima appear on either side of the main susceptibility pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 37 publications
5
33
0
Order By: Relevance
“…Similar experimental studies have revealed other wing-structure phase diagrams in UGe 2 [8,30,31] (also shown in Fig. 6 for comparison), Sr 3 Ru 2 O 7 [37], ZrZn 2 [9], UCoAl [35,36,40]. The behavior near the tricritical point could not be studied in Sr 3 Ru 2 O 7 and UCoAl because those compounds are already in the paramagnetic regime at ambient pressure.…”
Section: Quantum Wingsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar experimental studies have revealed other wing-structure phase diagrams in UGe 2 [8,30,31] (also shown in Fig. 6 for comparison), Sr 3 Ru 2 O 7 [37], ZrZn 2 [9], UCoAl [35,36,40]. The behavior near the tricritical point could not be studied in Sr 3 Ru 2 O 7 and UCoAl because those compounds are already in the paramagnetic regime at ambient pressure.…”
Section: Quantum Wingsupporting
confidence: 62%
“…In UCoAl, the anomaly corresponding to the field induced transition to the FM state shows two peaks in the ac susceptibility [35] and two kinks forming a plateau in electrical resistivity [36]. Two peaks in the ac susceptibility have also been reported in the metamagnetic transition of Sr 3 Ru 2 O 7 [37]. Although the magnetism in these systems originates from different electronic shells, it is remarkable that the multiple ferromagnetic states seems universal.…”
Section: Quantum Wingmentioning
confidence: 90%
“…k For x = 0 to x 0.7. l Phase diagram not mapped out completely; the most detailed measurements show tips of wings. See Wu et al (2011). m Paramagnetic at ambient pressure.…”
mentioning
confidence: 99%
“…Hydrostatic pressure drives the system away from FM, uniaxial stress drives it towards FM. See Wu et al (2011) and references therein, especially Ikeda et al (2000).…”
mentioning
confidence: 99%
“…In this critical region, only few experiments were carried out because of the severe experimental conditions of low temperature, high pressure, and high field. [1][2][3]5 Due to the recent focus on quantum criticality, the metamagnetism in itinerant ferromagnets has been recently revisited theoretically (see e.g. Ref.…”
Section: Introductionmentioning
confidence: 99%